Propagation dynamics of spin excitations along skyrmion strings - S. Seki (Nature Portfolio, 2020)
The propagation dynamics of skyrmions in three dimensions have attracted increasing attention. Here, the authors demonstrate the coherent and non-reciprocal propagation of spin excitations along skyrmion strings for the chiral-lattice magnet Cu2OSeO3 over a distance exceeding 50 μm.